Erranze libridinose Ricerche erudite su testi rari e dimenticati - Cherchi, Paolo (Studi filologici e letterari, 2023)
This "rambling among rare texts" collects research done almost all in the last five years, and having in common the "erudite" register, typical of works that explore little-visited when not exactly unknown areas, and that compulse rare texts, distributed over a wide time span, between the Middle Ages and the threshold of the nineteenth century. They also share in common a certain desire for freedom from the great theses of our period that insist on social and civic engagement, assigning to literature the task of revealing the ills of our world and offering remedies to improve it; but they also move away from formalist research that focuses on functions and forgets values altogether. Research, then, for the pleasure of research. But it is not irresponsible hedonism: the author seeks to ascertain historical facts, to reconstruct traditions worthy of being known and valued. If anything, it is the hedonism of historical and philological research that, if not advancing theses, at least reevaluates the existence of forgotten works that now, placed back in their historical context, acquire the value of buried treasures brought to light. It is an exhibition of "rarities" and unusual explorations that, thanks to the kind of historical-philological analysis practiced by the author, surprise on every page and help one understand that even scholarly research provides pleasures and surprises that are by no means unexpected.